TANGOW: a model for internet-based learning. (1st January 2001) - Carro, Rosa Maria; Pulido, Estrella; Rodriguez, Pilar
Learning is one of the most interesting applications of internet-based systems. At present, several approaches are being carried out in order to make this process adaptive. In this context, "adaptivity" mainly refers to adapting the instructional material to different students under certain conditions: i) the instructional material is available as a whole and ii) potential students can be essentially different. Moreover, it is not possible to talk about "adaptivity" whenever a complete set of courses about the same subject is available; each is designed for a specific student profile. In this framework, the TANGOW system aims to provide a model in which most of the desirable features of internet-based learning processes are taken into account. TANGOW stands for Task-based Adaptive learNer Guidance On the WWW.